On Becoming a Failure as a School Counsellor - Vitro, Frank T.; Yvon, Bernard R. (Canadian Journal of Counselling and Psychotherapy, 2012)
In light of the plethora of articles on "how to become more effective in" covering a variety of professions and areas of competency, the authors of "On Becoming a Failure as a School Counselor" have taken a more cynical approach by identifying the negative or undesireable traits to be avoided by helping professionals.The obvious assumption is that in satire form the message can be conveyed in alighter, more humorous context while the serious intent remains implicit. This is the third in a series of similar publications by the authors, the first two being: "10 Easy Ways to Become an Incompetent Teacher" in Educational Perspective, 1973; and "Bea Loser as a Parent" in Academic Therapy, 1975.